Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/mren.200600034
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization and Characteristics of Polyurethane/Organoclay Nanocomposites

Abstract: Different polymerizable ammonium surfactants were successfully synthesized via Michael‐addition and quaternarization reactions. Organoclays containing reactive methacrylate groups were prepared by the cationic exchange process. Intercalated nanocomposites were produced by UV initiated polymerization with 5 wt.‐% organophilic clay loading. DMTA tests and tensile analysis implied that a long chain polymerizable modifier could crosslink with the polymer matrix, and mechanical and tensile properties were enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Furthermore, some researchers suggested that the exfoliation degree of the polymerizable clay could be influenced by the position of the reactive functional group, 16,24,37 and a crosslinking structure was found during the preparation. 25,28,32,33,37 However, the reason why the polymerizable clay is more exfoliatable than the nonpolymerizable clay is still unclear. Obviously, such knowledge could be very useful in designing exfoliated nanocomposites with enhanced interfacial interaction.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, some researchers suggested that the exfoliation degree of the polymerizable clay could be influenced by the position of the reactive functional group, 16,24,37 and a crosslinking structure was found during the preparation. 25,28,32,33,37 However, the reason why the polymerizable clay is more exfoliatable than the nonpolymerizable clay is still unclear. Obviously, such knowledge could be very useful in designing exfoliated nanocomposites with enhanced interfacial interaction.…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24][25][26][27][28][29][30] It can also be used in the preparation of other polymer/ clay nanocomposites. 16,[31][32][33][34][35][36] According to these researches, the resultant nanocomposite is usually intercalated whether the modified clay by nonpolymerizable agent is intercalated or not in the system before polymerization; but the resultant nanocomposite is usually partially exfoliated when the modified clay by polymerizable agent is intercalated in the system before polymerization. If the modified clay is exfoliated in the system before polymerization, no matter the clay is polymerizable or not, the resultant nanocomposite is surely exfoliated.…”
Section: Introductionmentioning
confidence: 99%
“…Clay composite materials continue to be of interest to the discipline due to the economic and physical advantages of related products. Many of these clay composite materials may undergo an intercalation (i.e., spreading via insertion of compatible compounds between the clay platelets) or exfoliation process (i.e., separation of the clay platelets) whereupon they may be characterized as nanocomposite materials with exceptional properties, depending on the interplate d‐spacing (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the literature has been filled with clay composite materials used in photopolymerization . The vast majority of the literature discusses the physical functionalization of the clays via ion exchange methods to introduce either polymerizable monomers, film‐forming additives, or, in rare cases, photoinitiators whereupon the ion exchange functionalization produces an organic‐inorganic hybrid material that is more readily integrated or compatiblized into the formulation and resulting polymer . For example, Tan et al .…”
Section: Introductionmentioning
confidence: 99%
“…[2,3]. These surfactants play an important role in microemulsion systems to prepare nanoporous polymeric materials [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%